Pengaruh Tindakan Afirmatif dan Budaya Organisasi Terhadap Manajemen Kinerja PT. Bintang Sayap Utama Area Jawa Timur - Via Lailatur Rizki (Ecobuss, 2021)
This research aims to determine the effect of affirmative action and organizational culture on performance management on PT. Bintang Sayap Utama Area East Java One. The type of research used is causal research. The population used is all employees of PT. Bintang Sayap Utama Area East Java One with coverage of Lumajang, Batu and Malang regency as many as 66 employees with census method. The analytical method used in this study is multiple linear regressions. The results showed that affirmative action had no significant effect on pt performance management. Bintang Sayap Utama Area East Java One. Organizational Culture has a significant impact on work management PT. Bintang Sayap Utama Area East Java One. Keyword: Affirmative Action, Organizational Culture, Work Management